Consider the following function.f(x) = 1 − x2/3Find f(−1) and f(1).f(−1)= f(1)
Question
Consider the following function.
Find and .
Solution
To find the values of f(-1) and f(1), we simply substitute these values into the function f(x) = 1 - x^(2/3).
For f(-1), we substitute x with -1:
f(-1) = 1 - (-1)^(2/3) = 1 - 1 = 0
For f(1), we substitute x with 1:
f(1) = 1 - 1^(2/3) = 1 - 1 = 0
So, f(-1) = f(1) = 0.
Similar Questions
Consider the following function.f(x) = 1 − x2/3Find f(−1) and f(1).f(−1)= f(1)
What are the zeroes of f(x) = x2 − 2x − 3? x = −3, 1 x = −3, −1 x = 3, 1 x = 3, −1
A function f(x) increases by a factor of 1.9 over every unit interval in x and f(0)=2.Which could be a function rule for f(x)?
Given f, of, x, equals, minus, x, squared, minus, xf(x)=−x 2 −x, find f, of, minus, 9f(−9)
Given f, left bracket, x, right bracket, equals, minus, 5, x, minus, 3f(x)=−5x−3, find f, left bracket, minus, 6, right bracketf(−6).
Upgrade your grade with Knowee
Get personalized homework help. Review tough concepts in more detail, or go deeper into your topic by exploring other relevant questions.